Medieval Latin: An introduction and bibliographical guide - Mantello, F.A.C.; Rigg, A.G. (Washington D.C. CUA Press, 1996)
A new standard guide to the Latin language and literature of the period from C.A.D 200 to 1500. Comprehensive in scope, this guide to the learned lingua franca of western Europe satisfies a longstanding need for a reference tool in English that focusses on medieval latinity in all of its specialized aspects. It provides introductions to, and bibliographic orientations in, all the main areas of Medieval Latin language, literature, and scholarship.